Parental Awareness and Attitudes Towards ACL Injury Prevention Programs in Youth Athletes: Original Research - Sparagana, Paola; Selee, Bayley; Ellis, Henry; Ellington, Matthew; Beck, Jennifer; Carsen, Sasha; Crepeau, Allison; Cruz, Aristides; Heyworth, Benton; Mayer, Stephanie; et al. (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Background: The incidence of anterior cruciate ligament (ACL) injuries has steadily increased in young athletes and may have long-term implications for physical function and quality of life. ACL injury prevention programs have been developed and refined over the past several decades and have been shown to reduce the risk of ACL injuries by up to 70%1,2. However, awareness and understanding of these programs among parents of athletes is unknown. This study aims to evaluate knowledge and attitudes towards ACL injury prevention programs for parents of young athletes involved in cutting and pivoting sports at varying levels of competition. Methods: A cross-sectional survey was nationally distributed to a convenience sample of parents of young athletes between the ages of 5 and 18. The survey focused on questions relating to demographic information, history of ACL injury, knowledge of ACL injury prevention programs, and factors influencing program awareness. Descriptive statistics were used to summarize participant characteristics and determine prevalence of program awareness. Results: A total of 244 parents completed the survey with 74% indicating their child’s primary sport was soccer. Seventy-seven percent of these athletes began specializing in their primary sport at an average age of 8 years old (SD = 2.72). Only 18% of parents reported knowledge of ACL injury prevention programs and just 6% reported their child has ever participated in one. Of the 29 (12%) athletes who had experienced an ACL injury, only 17% had ever participated in an ACL injury prevention program. The most common reported barrier of ACL injury prevention program participation was the lack of awareness of where to get such training and it not being readily offered to their child. Sixty-eight percent of all parents would have their child participate in an ACL injury prevention program if offered to them. Conclusion: There is a lack of awareness of ACL injury prevention programs among parents of young athletes involved in high injury-risk sports. However, most parents would be interested in their child utilizing an ACL injury prevention program if it were offered.